MUSEOS Y COMUNICACIÓN: LOS NUEVOS MEDIOS COMO HERRAMIENTA DE DIÁLOGO Y SOCIABILIDAD DE LA INSTITUCIÓN. EL USO DE TWITTER POR EL MUSEO DEL PRADO, MUSEO THYSSEN-BORNEMISZA Y MUSEO REINA SOFÍA - Dr. David CORDÓN BENITO,Diana GONZÁLEZ GONZÁLEZ (Fonseca, Journal of Communication, 2023)
Different changes in the political, social and economic environment force museums to adapt themselves constantly along their history to new challenges to develop their role as social institutions. From a conception based on the collection, this organisation transferred its focus to the public, which helped museums to understand the need of communication as a strategic tool for dialogue with their stakeholders.